'We call this "play", however…': Navigating 'play anxiety' in early childhood education and care markets. (June 2019) - Drew, Christopher
Neoliberal rationalities predicated on consumer choice and market forces have increasingly positioned parents as consumers in early childhood and care markets. In this context, providers jostle to attract clientele by providing pathways through and around a milieu of parental anxieties and ambitions for their children. This article examines a chief marketing document – the early childhood education and care provider's website – and reflects on the ways providers address parental 'play anxiety' in marketised times. It finds that differing and even contradictory discursive ideals about children's risky, risk averse and guided play move in and out of the texts in ways that work to appeal to parents' anxieties and desires. The emergence of a mosaic of differing discourses of play in marking texts highlights the complexities and contradictions that come with early childhood education and care provision, parenting and growing up in marketised neoliberal times.